Influence of 3D-printing on the behaviour of Ti6Al4V in high-speed friction. (December 2020) - Marquer, Mathieu; Laheurte, Pascal; Faure, Laurent; Philippon, Sylvain
Abstract: Additive manufacturing techniques, such as Selective Laser Melting (SLM) are considered for making some Ti6Al4V parts. However, in some assemblies, such parts may be subjected to severe sliding. A Ti6Al4V tribopair was subjected to sliding under high speed and pressure (40 m/s and up to 300 MPa). This research focuses on the influence of the manufacturing process (machining or SLM) and the building orientation (for SLM) of one tribopair element on the friction coefficient and wear. Results were mostly insensitive to SLM orientation. However, with the SLM parts, there was a higher friction coefficient and a lower wear than with machined parts. An energy-based approach revealed a single pattern for wear regardless of the manufacturing technology, consistent with previous results. Highlights: Friction coefficient and wear were measured for tests with SLM and machined pads. Friction coefficient and wear were mostly independent from SLM orientation. SLM Ti6Al4V had a higher friction coefficient and lower wear than machined Ti6Al4V. A single energy-dependent trend was followed by wear from tests with both materials.